Programmable System-on-Chip (PSoC) Embedded Readout Designs for Liquid Helium Level Sensors. (August 2014) - Parasakthi, C.; Gireesan, K.; Usha Rani, R.; Sheela, O. K.; Janawadkar, M. P.
This article reports the development of programmable system-on-chip (PSoC)-based embedded readout designs for liquid helium level sensors using resistive liquid vapor discriminators. The system has been built for the measurement of liquid helium level in a concave-bottomed, helmet-shaped, fiber-reinforced plastic cryostat for magnetoencephalography. This design incorporates three carbon resistors as cost-effective sensors, which are mounted at desired heights inside the cryostat and were used to infer the liquid helium level by measuring their temperature-dependent resistance. Localized electrical heating of the carbon resistors was used to discriminate whether the resistor is immersed in liquid helium or its vapor by exploiting the difference in the heat transfer rates in the two environments. This report describes a single PSoC chip for the design and development of a constant current source to drive the three carbon resistors, a multiplexer to route the sensor outputs to the analog-to-digital converter (ADC), a buffer to avoid loading of the sensors, an ADC for digitizing the data, and a display using liquid crystal display cum light-emitting diode modules. The level sensor readout designed with a single PSoC chip enables cost-effective and reliable measurement system design.